Mental disorders in the community dwelling elderly - Kirby, Michael (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2000)
The elderly population is increasing both in numbers and as a proportion of the overall population. Mental disorders are common among the elderly. Most older people with mental disorders live in the community and attend primary care rather than specialist psychiatric services. Many studies have shown low rates of detection and treatment of mental disorders in the elderly population. There are no published data on the range of mental disorders among the community dwelling elderly in an Irish context. This thesis describes the range of mental disorders among older people in a Dublin community and considers issues which contribute to the detection and treatment of these disorders.
Keywords: Psychiatry, M.D.; M.D. Trinity College Dublin